Innovative and effective subject randomization methods - Zhao, Wenle (Henry Stewart Talks, 2020)
Advantages and disadvantages of permuted block design, Block urn design for high allocation randomness, Mass-weighted urn design target any unequal allocation, Minimal sufficient balance for many baseline covariates